Spatial and Structural Factors Shape Seagrass-Associated Bacterial Communities in Singapore and Peninsular Malaysia - Rabbani, Golam; Yan, Bertrand Chengxiang; Lee, Nicole Li Ying; Ooi, Jillian Lean Sim; Lee, Jen Nie; Huang, Danwei; Wainwright, Benjamin J. (Frontiers in Marine Science, 2021)
Plant-microbe relationships play critical roles in the functioning and health of terrestrial plants, but little is known about this relationship in marine angiosperms such as seagrasses. Here, we investigated the microbial communities associated with the seagrass Enhalus acoroides throughout Singapore and Peninsular Malaysia. At each sampling location we collected 10 individual and unconnected plants. Each plant was subsequently broken down into leaves, roots, and rhizomes. In addition to living plant parts a sediment sample was taken in close proximity to each. Using high throughput 16S rRNA gene amplicon sequencing we characterised the bacterial communities associated with each plant part and the associated sediment sample. Results indicate geographic structuring of bacterial communities, with a significant pattern of distance decay suggesting dispersal limitation is a contributing factor to the differences we see in bacterial community structure. Bacterial communities can be further differentiated by the function of the collected sample (leaf, root, and rhizome), and we identified a number of microbial indicator species that are associated with each plant part. Further analysis revealed the presence of several microbial taxa that have previously been identified as indicators of “unhealthy” or “stressed” seagrass meadows. This study addresses a current scientific gap related to the characterisation of seagrass microbiomes, and provides a foundation on which future studies can build, particularly those in the Southeast Asian seagrass biodiversity hotspot.